Problems and Prospectus of Agripreneurs-An Empirical Study (International Journal of Innovative Research in Engineering & Management, 2022)
India is an agricultural nation with good  land availability for agricultural activities, and a sizable  population is still engaged in agriculture and enterprises that  are related to it. Agripreneurship may boost the economy,  increase revenue, and open many business opportunities in  rural regions. Effective agricultural entrepreneurship efforts  may also help the agripreneurs who are dealing with long term economic issues including urbanization, poverty, and  unemployment. They deal with issues like financial  difficulties in supporting farmers, promoting agricultural  products, transportation, women's emancipation, tribal youth  development, and a few others. These issues include income  diversification, growth, increased employment, new  technology, and the best possible use of the available  resources.The main issue with liberalization, privatization and  globalization is that the entire region has become like a  neighbouring market in which our farmers and commodities  will have to compete with foreign companies in terms of  quality and price. The Indian economy is primarily agrarian.  Agriculture directly employs around 65 percent of the Indian  people and accounts for 16-17 percent of India's GDP. The present survey is being conducted in the Ongole area of  the Prakasam district, Andhra Pradesh. The paper is aimed at  problems &prospects of agriprenures. The questionnaire is  prepared with 21 relevant questions to collect primary data.  Respondents were asked to respond on five points lickered  scale. The questionnaire is given to 128 people among  agriprenures and 105 are returned and 90 responded  properly. To analyses, the primary M.S excel has been used.  Channel of distribution & Financial support is as  significantly affecting the agrepreneurs.
Keywords: Agriprenure; Urbanization; Liberalization; Globalization; Prospects; M.S excel